Digital transformation in Portuguese architecture studios: Insights from the field - Silva, D.; Paio, A. (SIGraDi 2024 Proceedings Book, 2024)
The integration of digital tools in architecture is revolutionizing the field, affecting design processes, construction precision, and project management. This study explores the digital transformation of Portuguese architecture studios, focusing on the adoption and impact of digital tools such as Building Information Modeling (BIM) and digital fabrication. Through qualitative analysis of interviews with nine architectural practices, the research identifies key motivations, strategies, and outcomes associated with digital integration. The findings highlight significant benefits, including enhanced project coordination, precision, and efficiency, alongside persistent challenges like high costs, resistance to change, and regulatory barriers. The study underscores the strategic importance of digital tools in advancing architectural practice and calls for supportive policies, educational reforms, and industry collaboration to overcome adoption hurdles. By addressing these challenges, Portuguese studios can fully leverage digital technologies to foster innovation, improve project outcomes, and contribute to the evolution of architectural practices.